Modernization of the State: The Role of Open Government in the Effectiveness of Municipal Management in San Martín, Peru - Mabel, Contreras-Julián Rosa; Manuel, Delgado-Bardales José; Keller, Sánchez-Dávila; Pilar, Palomino-Alvarado Gabriela del (Journal of Ecohumanism, 2024)
The study aimed to establish the relationship between open government and the effectiveness of municipal management in the San Martín region, employing a basic quantitative research approach, a non-experimental design, and a descriptive correlational and cross-sectional scope. The population comprised 926,000 citizens, from which a sample of 1,537 was selected. The survey technique was used with two questionnaires, one for each variable. Regarding the dimensions of open government, the results showed a transparency level categorized as regular at 60%, deficient at 30%, and good at 10%; public sector integrity was rated as regular at 62%, deficient at 27%, and good at 12%; accountability was evaluated as regular at 46%, deficient at 38%, and good at 16%; and citizen and stakeholder participation achieved a regular level of 55%, deficient at 35%, and good at 10%. Concerning the effectiveness of municipal management, the evaluated dimensions showed that equipment and information and communication technologies were classified as regular at 60%, good at 20%, and deficient at 14%; human resources were assessed as regular at 64%, deficient at 21%, and good at 15%; municipal competencies and functions were rated as regular at 67%, good at 17%, and deficient at 16%; and local public services were reported as regular at 63%, deficient at 19%, and good at 18%. Finally, it was concluded that there is a high and significant positive relationship between open government and the effectiveness of municipal management, with a Spearman’s Rho coefficient of 0.824 (high positive correlation) and a p-value of 0.000 (p ≤ 0.01), estimating an incidence of 74% between both variables.